Some General Relativistic Fluid Spheres: Exploring the interior metric and physical parameters of general relativistic fluid spheres (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The present paper provides new solution of Einstein’s field equations for the interior Metric of a fluid sphere with and without cosmological constant and by taking suitable conditions on g44. Various physical parameters have been found and discussed.